2004
DOI: 10.1093/alcalc/agh079
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiotensin Ii and the Subfornical Organ in the Pharmacological Actions of Ethanol

Abstract: Collectively, the results demonstrate that ethanol-induced temperature responses are mediated by the renin-angiotensin system and that this interaction is mediated centrally. In addition, the results demonstrate that the SFO is a site that mediates several neurobiological effects of ethanol, possibly via the renin-angiotensin system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…20 Interestingly, lesion studies suggest that the SFO may mediate some thermogenic effects of Ang-II in rats. 34 Moreover, sRA double transgenic mice which exhibit abundant Ang-II in the SFO exhibit increased metabolic rate. 5 It was therefore surprising that SFO-targeted deletion of the AT 1a R did not attenuate the induction of resting metabolism by DOCA-salt.…”
Section: Discussionmentioning
confidence: 99%
“…20 Interestingly, lesion studies suggest that the SFO may mediate some thermogenic effects of Ang-II in rats. 34 Moreover, sRA double transgenic mice which exhibit abundant Ang-II in the SFO exhibit increased metabolic rate. 5 It was therefore surprising that SFO-targeted deletion of the AT 1a R did not attenuate the induction of resting metabolism by DOCA-salt.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypothalamic regions expressing ANG II, such as the POA and paraventricular nucleus, are possible sites at which ANG II may influence thermoregulation during exercise (14). Therefore, we hypothesized that infusion of Los into the cerebral ventricle would perfuse to the SFO and other thermoregulatory centers situated in the hypothalamus, inhibiting the heat loss response and accelerating the BHR and HSR during prolonged exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has recently been shown that inhibition of the POA/AH by local infusion of tetrodotoxin impairs heat loss in running rats (16). A variety of studies have suggested that SFO and other adjacent areas are critical for the central actions of ANG II (7,14) and that SFO afferent communication with paraventricular nucleus utilizes ANG II as a neurotransmitter within this hypothalamic region (25). Moreover, lesion of the SFO resulted in abolished ANG II-mediated temperature response (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is supported by the finding that enalapril did not alter esophageal or mean skin temperature in humans during exercise in the heat (Mittleman, 1996) and that peripherally administered losartan had no effect on temperature regulation in control rats during heat stress (Horowitz et al, 1999). However, peripherally administered losartan did prevent the decrease in colonic temperature that follows administration of ethanol (Grobe et al, 2004) and did affect the later colonic temperature response to isoproterenol (Fregly and Rowland, 1993). Furthermore, the colonic temperature threshold for salivation in heat acclimated rats was increased by peripheral administration of losartan (Horowitz et al, 1999).…”
Section: Discussionmentioning
confidence: 79%